CODESRIA Bulletin, No 4, 2021 - Journal System (CODESRIA Bulletin, 2021)
<div class="ajaxbloc ajax-id-wysiwyg bind-ajaxReload" data-ajax-env="tWrnkpJ1aYEOIlBUK2H0nEy6TlewZgoAVvSN62zSHw/u3+UMCmeMp7BLOBuv/wXOQPN1a3LcCW3RBILRsoGpgr2l7FTBy8s7c1yII10L0Mj8nLtLTYk5eoNHOeuSvsg6Uval3AkAVwaS40Zv5fILAdBNYV7ykWrlvh5ZFoGUvW/Obi1Uf8dCIhQbfFahEsXrPwnzNiRlrBA7fRg=" data-origin="./?exec=article&id_article=3228" aria-live="polite" aria-atomic="true"> In this issue Editorial Godwin R. Murunga & Ibrahim O. Ogachi .................................................1 Éditorial Godwin R. Murunga & Ibrahim O. Ogachi ..................................................4 1. Retrospecting to Prospect: Quo Vadis AFRICA? ’Funmi Olonisakin..............................................................................7 2. Rethinking African Politics: The New Age of Political Parties Peter Anyang’ Nyong’o.......................................................................17 3. The Dialectics of Maguphilia and Maguphobia Issa Shivji........................................................................................23 4. A Rejoinder to Shivji’s ’Dialectics of Maguphilia and Maguphobia’ Dastan Kweka................................................................................33 5. Why Development and Transformative Social Policy Matter: Lessons of COVID-19 in Africa Jìmí O. Adésínà............................................................................35 Reflections on Neither Settler Nor Native 6. Reading History from the Bottom Up - From Citizen and Subject to Neither Settler Nor Native Ibrahim Abdallah........................................................................44 7. Why has Europe’s Past Become Africa’s Postcolonial Present? Refections on Mahmood Mamdani’s Ideas on Decolonising the Political Community Sabelo J. Ndlovu-Gatsheni........................................................ 48 8. Reimagining Decolonisation Today: A Review of Neither Settler nor Native Adom Getachew........................................................................54 9. Neither Settler nor Native: A Response to My Critics Mahmood Mamdani..................................................................58